KAJIAN STRATEGI KOPING DAN PERILAKU INVESTASI ANAK PADA KELUARGA BURUH PEMETIK MELATI GAMBIR - Rosidah, Umu; Hartoyo, Hartoyo; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2012)
The objectives of this research were to investigate family coping strategy and the investment behavior on children of Jasmine officinale labor families. Research location was selected purposively based on size of Jasmine officinale area in study site. This research involved sixty six families were selected randomly. Data were collected by interview and were analyzed using regression analysis.The result of research showed that wife as Jasmine officinale labor gave important contribution to family income. Family welfare was influenced by father’s side job, father’s job, father’s education, and family income. Coping strategies that were done by labor family was classified as low category. Family size, family type, father’s side job, and family welfare has significant influence toward coping strategy. Mother’s education and family income correlated significant with investment behavior; family size, number of school-age child, father’s education, and family income had correlated significant with allocation of expenditure for children.